Prevalence of small for gestational age (SGA) and short stature in children born SGA who qualify for growth hormone treatment at 3 years of age: Population‐based study. Issue 5 (19th February 2016) - Fujita, Kaori; Nagasaka, Miwako; Iwatani, Sota; Koda, Tsubasa; Kurokawa, Daisuke; Yamana, Keiji; Nishida, Kosuke; Taniguchi‐Ikeda, Mariko; Uchino, Eiko; Shirai, Chika; Iijima, Kazumoto; Morioka, Ichiro
Abstract: Background: To treat children born small for gestational age (SGA) with severe short stature, treatment with growth hormone (GH) has been approved in the USA, Europe, and Japan, but no population‐based studies have reported their prevalence. The aims of this study were to investigate the prevalence of SGA and short stature in children born SGA who qualify for GH treatment at 3 years of age in a Japanese population. Methods: A population‐based study was conducted in Kobe, Japan with 27 228 infants who were born between 2006 and 2008 and followed until 3 years of age. Prevalence of birthweight (BW) or birth length (BL) ≤ −2.0 standard deviation scores (SDS) for gestational age (GA; definition of SGA) was calculated. Short children born SGA who qualify for GH treatment at 3 years of age were estimated using the following criteria: BW and BL below the 10th percentile for GA, BW or BL ≤ −2.0 SDS for GA, and 2.5 SDS below the mean height for age. Results: The prevalence of SGA was 3.5%. The estimated prevalence of short stature in children born SGA who met the criteria for GH treatment was 0.06%. The prevalence in infants born <34 weeks (0.39%) was significantly higher than that in infants born 34–41 weeks GA (0.05%, P = 0.02). Conclusions: The prevalence of SGA and short stature in children born SGA who qualify for GH treatment is approximately 1 of 30 infants and 1 of 1800 children, respectively. The risk is increased when children are born <34 weeks GA.